Evaluasi Kapabilitas Pengembangan Perangkat Lunak Menggunakan Capability Maturity Model Integration - Dev 1.3 (Studi Pada CV.Profile Image Studio) - Windi Prasetyo; Aditya Rachmadi; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
CV. Profile Image Studio is a company that focus in the website development, mobile applications, digital business, and online campaigns. The products produced are expected to support the customer's business processes that are running. The product is also expected to be carried out according to the time and costs set. But in the work there are several problems, among others, the change in needs and the existence of product defects after being given to customers. This study aims to assess the level of capability in the process of making products on CV. Image Studio Profile uses Capability Maturity Model Integration (CMMI) Development 1.3. This study uses qualitative methods by collecting data through the interview process and document tracking. The research stages use the Standard Appraisal CMMI Method for Process Improvement (SCAMPI) class C. Capability level assessment is carried out on the six process areas contained in the CMMI product roadmap. The six area processes include requirements development, requirements management, technical solutions, process and product quality assurance, configuration management and verification. Based on the results of the assessment, it was found that only the area technical solution process was performed at one stage, while the five other area processes were at the zero level / incomplete. From the results of the assessment, an analysis is then carried out containing a solution for the company to increase the capability level of each area process